Renewable Energy Challenges and Market Dynamics in a Renewables Dominated Power System: The Case of the German Power System - Abuzayed, Anas Ishtaiwi Salman; Liebensteiner, Mario; Hartmann, Niklas (2024 20th International Conference on the European Energy Market (EEM), 2024)
The massive addition of renewables poses various challenges to system operators. The success of the German energy transition relies heavily on the availability of flexibility in the energy system. This paper investigates the market challenges and opportunities of achieving climate neutrality by 2045 in Germany. The analysis shows that in the absence of adequate incentives for storage systems, investments in gas power plants as a bridging technology may be necessary to ensure a secure supply. However, the long-term feasibility of these plants, especially post 2045 is questionable and could lead to underinvestment. Overcapacities from solar affect the utilization of other renewables. Despite renewables solely covering the demand for nearly 4500 hours, they will not be enough to achieve system security. The significance of storage flexibility becomes pronounced. However, they only experience high deployment after 2035. The insights of this work are crucial for sustainable energy planning and market design.
CRIS-Team Scopus Importer:2024-09-06
Keywords: energy system flexibility; energy transition; market dynamics; policy interventions; renewable energy challenges